Pengaruh Jenis Bahan Bakar Terhadap Emisi Gas Buang Injection Otto Engine System - Saksono , Puji; Aji Sudikna, Bayu; Ferdnian, Marsius; N.S. Sidabutar, Sadat (Journal of Applied Mechanical Engineering and Renewable Energy, 2025)
The use of motorized vehicles currently experiences a very significant increase, this has an impact on increasing air pollution due to exhaust gas emissions from combustion. One of step to minimize the level of air pollution due to exhaust emissions is to choose the right fuel, so that the combustion in the combustion chamber is perfect. Based on this, a problem was formulated related to the influence of fuel’s type on exhaust gas emission values in vehicles with injection otto engine system technology. The research object is the 2017 Toyota Sienta 1.5 G M/T car using electronic fuel injection. The types of fuel used in this research are Pertalite, Pertamax, and Pertamax Turbo. The Test results from the use of Pertalite, Pertamax and Pertamax Turbo fuel types show that the exhaust gas emission values for CO, HC and CO2 content will decrease when the engine speed is higher. The best type of fuel from the test results is Pertamax Turbo RON 98, because almost all test results for CO, HC and CO2 content at various types of engine speed show the lowest results. In accordance with the Minister of Environment Regulation No.06 of 2006 concerning Exhaust Gas Emission Thresholds for Old Motor Vehicles, the vehicle tested was declared to have passed the exhaust emission test. Minister of Environment Regulation, 2006 determines the maximum threshold values for CO = 1.5% and HC = 200 ppm.